واقع موضوعات الرواية الاجتماعية العربية والملايوية دراسة مقارنة = The reality of Arabic and Malay social novel themes a comparative study - Kashif, Ain Nadzirah; Salleh, Abdul Halim; Ahmad Safian, Nursafira (2019)
تتمحور هذه الدراسة حول الكشف عن واقع الرواية الاجتماعية العربية والملايوية، وذلك من خلال استقراء المعلومات ووصفها لمعرفة أبعاد الموضوعات المهمة في الرواية الاجتماعية العربية والملايوية، وسوف تسلك هذه الدراسة المنهج الإمريكي في الدراسة المقارنة لمعرفة أوجه التشابه والاختلاف بين الرواية الاجتماعية العربية والملايوية دون الخوض في عوامل التأثير والتأثر التي يتطلب التتبع التاريخي كما في المنهج الفرنسي. وبما أن النزعة الإسلامية فد أثرت على الرواية الاجتماعية العربية والملايوية لذا فإن الدراسة ستناقش واقع الرواية الاجتماعية الإسلامية في العربية والملايوية في نهاية الدراسة، وقد توصلت الدراسة إلى أن هناك أوجه مختلفة من التشابه والاختلاف من الموضوعات لعوامل مختلفة وأسباب ومتباينة. ************************************************************************************* This study revolves around revealing the reality of Arabic and Malays social novel, through extrapolating and describing information methods to explore the dimensions of the important topics in the Arabic and Malay social novels. This study will pursue American curriculum of comparison study which is not concerned with the factors of influence and vulnerability that require historical traceability of the French curriculum to identify the similarities and differences between the Arabic and Malay social novel. Therefore, since the Islamic trend has influenced the Arabic and Malay social novel, the study will discuss the reality of the Islamic social novel in Arabic and Malay at the end of the study. The study found that there are different forms of similarities and differences of social narrative’s themes due to different factors and reasons.